A Healthy Heart and a Healthy Brain: Looking at Mitophagy - Luo, Hongke; Zhang, Ruohan; Krigman, Judith; McAdams, Allison; Ozgen, Serra; Sun, Nuo (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial dysfunction is a hallmark of aging and is a major contributor to neurodegenerative diseases and various cardiovascular disorders. Mitophagy, a specialized autophagic pathway to remove damaged mitochondria, provides a critical mechanism to maintain mitochondrial quality. This function has been implicated in a tissue’s ability to appropriately respond to metabolic and to bioenergetic stress, as well as to recover from mitochondrial damage. A global decline in mitophagic flux has been postulated to be linked to pathological alterations that occur in the heart and the brain as well as a general age-dependent decline in organ function. Cellular observation suggests multiple mechanistically distinct pathways converge upon and activate mitophagy. Over the past decade, additional molecular components within mitophagy have been discovered, including several disease-associated genes that are functionally implicated in mitophagy. However, the pathophysiological role of mitophagy, and how it is regulated within normal physiology or various disease states, is less well established. Here, we will review the evidence that a decline in mitophagy contributes to impaired mitochondrial homeostasis and may be particularly detrimental to postmitotic neurons and cardiomyocytes. We will discuss mitophagy’s pathological significance in both neurodegenerative diseases and cardiovascular disorders. Additionally, signaling pathways regulating mitophagy are reviewed, with emphasis placed on how these pathways might contribute to disease progression. Understanding mitophagy’s role in the mechanisms of disease pathogenesis should allow for the development of more efficient strategies to battle pathological conditions associated with mitochondrial dysfunction.